2013
DOI: 10.1371/journal.pone.0063898
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and QTL Mapping of Seed Coat Color in Sesame (Sesamum indicum L.)

Abstract: Seed coat color is an important agronomic trait in sesame, as it is associated with seed biochemical properties, antioxidant content and activity and even disease resistance of sesame. Here, using a high-density linkage map, we analyzed genetic segregation and quantitative trait loci (QTL) for sesame seed coat color in six generations (P1, P2, F1, BC1, BC2 and F2). Results showed that two major genes with additive-dominant-epistatic effects and polygenes with additive-dominant-epistatic effects were responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 45 publications
4
100
0
3
Order By: Relevance
“…According to most of the previous studies on the inheritance of sesame seed coat color, this trait is determined by major genes at the embryo (Gutiérrez et al, 1994;Ashri, 2006;Falusi, 2007;Zhang et al, 2013). Although these reports did not present results of reciprocal crosses, it is possible to conclude that there was segregation for F 2 , which discards the maternal effect.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to most of the previous studies on the inheritance of sesame seed coat color, this trait is determined by major genes at the embryo (Gutiérrez et al, 1994;Ashri, 2006;Falusi, 2007;Zhang et al, 2013). Although these reports did not present results of reciprocal crosses, it is possible to conclude that there was segregation for F 2 , which discards the maternal effect.…”
Section: Resultsmentioning
confidence: 96%
“…Gutiérrez et al (1994), Falusi (2007), and Zhang et al (2013) concluded that inheritance was controlled by major genes at the cell nucleus. Shim et al (2005) and Ashri (2006) reported that minor genes were the ones responsible for this trait; however Ashri (2006) also observed that the white color was a recessive character.…”
Section: Introductionmentioning
confidence: 99%
“…In the black lines of Phaseolus vulgaris the protein content, iron and zinc are higher, in lines of other colors are richer in calcium, while the "carioca" is high in magnesium and manganese (Silva et al 2012). For the case of sesame, color is an important aspect as it is associated with biochemical properties, antioxidants and resistance to diseases (Zhang et al 2013). In Brassica juncea the yellow color was found in the genotype of the mother, and brown the father, the latter being the dominant (Xu et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Singharaj & Onsaard (2015) carried out SDS-PAGE in sesame genotypes with varied seed coat colour, for its food value. According to recent study, seed coat colour in sesame is more helpful in phylogenetic study than geographic origin of genotypes (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of protein markers with seed coat colours would further help in assessing genotypes for those biochemical traits which are linked to particular seed coat colours (Zhang et al, 2013). Such correlation, if exists, can be employed to identify diverse and superior sesame genotypes for future crop improvement programme.…”
Section: Introductionmentioning
confidence: 99%